A scoring system predicting the clinical course of CLPB defect based on the foetal and neonatal presentation of 31 patients. Issue 6 (7th July 2017) - Pronicka, Ewa; Ropacka‐Lesiak, Mariola; Trubicka, Joanna; Pajdowska, Magdalena; Linke, Markus; Ostergaard, Elsebet; Saunders, Carol; Horsch, Sandra; van Karnebeek, Clara; Yaplito‐Lee, Joy; Distelmaier, Felix; Õunap, Katrin; et al.
Abstract: Recently, CLPB deficiency has been shown to cause a genetic syndrome with cataracts, neutropenia, and 3‐methylglutaconic aciduria. Surprisingly, the neurological presentation ranges from completely unaffected to patients with virtual absence of development. Muscular hypo‐ and hypertonia, movement disorder and progressive brain atrophy are frequently reported. We present the foetal, peri‐ and neonatal features of 31 patients, of which five are previously unreported, using a newly developed clinical severity scoring system rating the clinical, metabolic, imaging and other findings weighted by the age of onset. Our data are illustrated by foetal and neonatal videos. The patients were classified as having a mild ( n = 4), moderate ( n = 13) or severe ( n = 14) disease phenotype. The most striking feature of the severe subtype was the neonatal absence of voluntary movements in combination with ventilator dependency and hyperexcitability. The foetal and neonatal presentation mirrored the course of disease with respect to survival (current median age 17.5 years in the mild group, median age of death 35 days in the severe group), severity and age of onset of all findings evaluated. CLPB deficiency should be considered in neonates with absence of voluntary movements, respiratory insufficiency and swallowing problems, especially if associated with 3‐methylglutaconic aciduria, neutropenia and cataracts. Being an important differential diagnosis of hyperekplexia (exaggerated startle responses), we advise performing urinary organic acid analysis, blood cell counts and ophthalmological examination in these patients. The neonatal presentation of CLPB deficiency predicts the course of disease in later life, which is extremely important for counselling.